The Frequent Effects of Hydroxyl Radicals on the Oxidation of Crude Oil in Soil. Issue 11 (30th August 2018) - Xu, Jinlan; Cao, Qianqian; Zhang, Miaojia; Wang, Fan; Huang, Tinglin; Ren, Junhao
Abstract : The characteristics of hydroxyl radicals ( OH) frequently produced in the Fenton process and the effects of these radicals on the oxidation of hydrophobic total petroleum hydrocarbons (TPH) in soil are investigated. Twelve groups of Fenton oxidation experiments are conducted using two kinds of crude‐oil‐contaminated soil samples (S1 and S2) with different soil organic matter (SOM) contents. The results show that the decrease of TPH increases by 6774 mg kg −1 (S1) and 5875 mg kg −1 (S2) by using the frequent OH ( OHf). These results are two times the results obtained by using the single OH ( OHs) (S1: 3410 mg kg −1, S2: 2918 mg kg −1 ). The decrease of hydrophobic long‐chain alkanes C21 –C30 is greatly improved by using the OHf, that is, oxidation of 1557–3011 mg kg −1 in soil S1 and 1371–2532 mg kg −1 in soil S2. Moreover, the C21 –C30 alkanes in soil S1 with low SOM (3.89%) are more degraded after oxidation. The residual non‐aqueous phase liquid (NAPL) TPH content by using the OHf (266–1200 mg kg −1 ) is much lower than that by using the OHs (2519–4070 mg kg −1 ). The residual of the NAPL TPH by using the OHf is 11–29% of the residual by using the OHs. This result indicates that residual NAPL TPH is reduced by using the OHf, and the TPH contents in the two soil samples are efficiently oxidized. Abstract : Total petroleum hydrocarbons (TPH) oxidation is two times greater in the frequent OH system than in the single OH system at the same OH yield, and the removal of long‐chain alkanes (C21–C30) is three times greater.